2022
DOI: 10.3390/ijerph19073927
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Differences between Men and Women during Overground Load Carriage at Self-Selected Walking Speeds

Abstract: Few studies have directly compared physical responses to relative loading strategies between men and women during overground walking. This study aimed to compare gait mechanics of men and women during overground load carriage. A total of 30 participants (15 male, 15 female) completed three 10-min walking trials while carrying external loads of 0%, 20% and 40% of body mass at a self-selected walking speed. Lower-body motion and ground reaction forces were collected using a three-dimensional motion capture syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Multiple studies have examined sex differences in gait mechanics during ruck marching (Krupenevich et al., 2015; Loverro et al., 2019; Middleton et al., 2022; Silder et al., 2013; Wills et al., 2021), with only one utilizing a sample consisting of primarily military personnel (Krupenevich et al., 2015). While findings for joint kinematics and kinetics have varied, studies have consistently reported a lack of sex differences in GRFs during ruck marching (Krupenevich et al., 2015; Middleton et al., 2022; Silder et al., 2013). This has included studies utilizing symmetrical and posterior loads, as well as participants with and without load carriage experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have examined sex differences in gait mechanics during ruck marching (Krupenevich et al., 2015; Loverro et al., 2019; Middleton et al., 2022; Silder et al., 2013; Wills et al., 2021), with only one utilizing a sample consisting of primarily military personnel (Krupenevich et al., 2015). While findings for joint kinematics and kinetics have varied, studies have consistently reported a lack of sex differences in GRFs during ruck marching (Krupenevich et al., 2015; Middleton et al., 2022; Silder et al., 2013). This has included studies utilizing symmetrical and posterior loads, as well as participants with and without load carriage experience.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that external loading during running, ruck marching, and drop landings may show sex‐ and age‐related differences in military trainees. For one, females (Almonroeder et al., 2017; Chumanov et al., 2008; Krupenevich et al., 2015; Loverro et al., 2019; Middleton et al., 2022; Phinyomark et al., 2014; Schache et al., 2003; Silder et al., 2013; Sinclair et al., 2012, 2015; Wills et al., 2021) and older individuals (Agresta et al., 2018; Boyer et al., 2017; Paquette et al., 2021) have shown significantly different kinematic patterns during these activities compared to their counterparts. The reasons for this are not clear, but it is likely related to a number of factors, such as differences in anthropometrics (Bredella, 2017) or muscular properties (Haynes et al., 2020; Nuzzo, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Walking condition has been adopted by many researchers mostly still using “normal” condition with unspecific subjects [ 38 , 54 , 67 , 102 ]. Subject specification is very influential from various aspects, such as abnormal [ 121 ], age [ 122 ], body mass index [ 123 ], gender [ 124 ], race/ethnic [ 125 ], religion [ 126 ], diseases experienced [ 127 ], and profession [ 128 ]. Adopting walking condition from a specific subject is crucial to the development of artificial hip joint for specific subjects.…”
Section: Research Gap and Future Researchmentioning
confidence: 99%
“…Its motions are varusvalgus occurring in the frontal plane; dorsiflexion-plantar flexion in the sagittal plane; foot progression and ankle rotation in the transverse plane (2,3). The three-dimensional motion analysis system is widely used to evaluate ankle movements (4)(5)(6)(7)(8). This method requires a normal reference from healthy population to differentiate from abnormal conditions.…”
Section: Introductionmentioning
confidence: 99%